INDONESIAN FARMERS CAN CONTRIBUTE IN REDUCING GREENHOUSE GASES EMISSION FROM WETLAND RICE FIELD - Iswandi Anas; Nia K. Megasari; Suprihati Suprihati; Hiroyuki OHTA (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2008)
Agricultural sector contribute significantly to the total GHG emission. There are some GHG mitigation options available but so far non of these mitigation options is being implemented by farmers. There is no real action have been taken by government to encourage farmers to implement the available mitigation option to reduce GHG emission from wetland rice field. We discuss some mitigation options and we suggest two additional GHG mitigation options namely crops rotation and System of Rice Intensification (SRI) that probably more attractive to farmer to implement them. However the impacts of these two proposed options as GHG mitigation options should be studied further.Key words: Greenhouse gases (GHG), mitigation option, farmer contribution, SRI, crop rotation